2012
DOI: 10.1364/boe.3.000972
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of optical coherence elastography measurements of shear wave propagation in homogeneous tissue equivalent phantoms

Abstract: In this work, we explored the potential of measuring shear wave propagation using optical coherence elastography (OCE) based on a swept-source optical coherence tomography (OCT) system. Shear waves were generated using a 20 MHz piezoelectric transducer (circular element 8.5 mm diameter) transmitting sine-wave bursts of 400 μs, synchronized with the OCT swept source wavelength sweep. The acoustic radiation force (ARF) was applied to two gelatin phantoms (differing in gelatin concentration by weight, 8% vs. 14%)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 41 publications
1
55
0
Order By: Relevance
“…The three phantoms with the bovine carotid arteries were imaged, and the results report the average and standard deviation of the 3 measurements. As expected, the values of the Young's moduli and shear moduli were greater for the part of the phantom with the higher concentration of gelatin [35,38]. The shear modulus and young modulus of carotid artery sample were 45.3 ± 0.6 kPa and 135.8 ± 1.8 kPa respectively.…”
Section: Results and Conclusionsupporting
confidence: 75%
See 1 more Smart Citation
“…The three phantoms with the bovine carotid arteries were imaged, and the results report the average and standard deviation of the 3 measurements. As expected, the values of the Young's moduli and shear moduli were greater for the part of the phantom with the higher concentration of gelatin [35,38]. The shear modulus and young modulus of carotid artery sample were 45.3 ± 0.6 kPa and 135.8 ± 1.8 kPa respectively.…”
Section: Results and Conclusionsupporting
confidence: 75%
“…The shear wave group speed was then calculated by using the ∆r and ∆φ obtained from the phase map, which depicts the distance between the two measurement locations and the calculated phase shift, respectively. These values were used to calculate the shear modulus and young modulus [35]. The mechanical properties of the inhomogeneous phantoms and carotid artery samples are shown in Table 1.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…In OCE, a mechanical load is applied to a sample, and the resulting deformation is detected using optical coherence tomography (OCT) [1]. There are many forms of OCE, differentiated by the method of mechanical loading, such as compressive [2][3][4], shear wave [5,6], surface wave [7,8], frequency-swept [9,10] and localized loading using magnetic nanoparticles [11]. Similarly, there are several methods for measuring the resulting sample deformation, including phase-sensitive detection [12,13], speckle tracking [2,4,14,15], and Doppler spectrum analysis [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…ARF in OCE makes use of 10s μs-10 ms bursts of ultrasound in the megahertz range to modulate the force applied to the sample. The resulting displacement has been detected as the axial displacement along the ultrasound beam at focus [83][84][85][86][87] or as an axial displacement associated with a shear wave generated by the burst at some lateral offset from the focus [88][89][90]. By scanning the frequency of the amplitude modulation, it has also been demonstrated that acoustic mechanical resonance can be detected along the axial direction [91].…”
Section: Loading Methodsmentioning
confidence: 99%
“…Whilst this localization is effectively point-wise loading for ultrasound elastography, it is more extended in the case of optics. For example, in [88], the depth of field of the ultrasound signal was ~3 mm and the full-width at half-maximum beam width was ~0.25 mm, an order of magnitude larger than the OCT resolution; and in [93], the ultrasound beam was assumed uniform over a 0.3 × 0.5 mm lateral region. Another potential benefit of ARF is that it could be integrated into catheter-based probes, as demonstrated at 10 mm diameter in [85].…”
Section: Loading Methodsmentioning
confidence: 99%